Conservation of Protected Forests in Catchment Areas of Reservoirs in Barelang, Riau Islands - Muhammad Dahari; Suwindar Agung Sutianto; Yuanita FD Sidabutar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Barelang is an abbreviation of Batam Rempang and Galang. Areas with rapid economic growth by utilizing a strategic location, namely international shipping lanes. The development of the city which has the issue of the availability of raw water sources is a special concern for the central government in developing this area later in the future. Sources of water that come from rainwater feds are then accommodated in reservoirs that have been built in several areas. BP batam's efforts in building this infrastructure are still continuing by collaborating with the central and regional governments, namely the Batam city government so that this problem can be solved together for the sake of the progress of barrelang in the future. The indicators that measure the availability of raw water in the Barelang Region are reservoirs that have been built by the government until 2022, including: Baloi Reservoir, Sei Harapan Reservoir, Muka Kuning Reservoir, Duriangkang Reservoir, Tembesi Reservoir, Sei Ladi Reservoir, Monggak Reservoir and Sei Gong Reservoir. Although these reservoirs are already available, the need for water for the survival of the city is still not sufficient. BP Batam's strategy to address the need for clean water takes the following steps: Normalization of Existing Reservoirs, Construction of new reservoirs, Seawater Desalination, Recycle domestic waste treatment, Supply of raw water from surrounding areas namely Bintan Island, Lingga Island, Siak River and Kampar River.